Generation and characterization of mice for conditional inactivation of Zeb1. Issue 4 (23rd February 2017) - Brabletz, Simone; Lasierra Losada, María; Schmalhofer, Otto; Mitschke, Julia; Krebs, Angela; Brabletz, Thomas; Stemmler, Marc P.
Abstract: The multizinc finger containing transcription factor ZEB1 plays crucial roles during various aspects of mammalian development and tumorigenesis. Best studied in human tumors, ZEB1 is activating the embryo‐derived program of epithelial‐mesenchymal transition (EMT). The aberrant activation of EMT confers an invasive metastasizing phenotype with acquisition of stem cell properties and resistance to radio‐ and chemotherapy. Although ZEB1 has very important functions in tumor progression, not much is known about its role in physiological contexts and during development and homeostasis. We describe the generation of Zeb1 flox/flox mice carrying a targeted mutation for conditional Zeb1 gene inactivation and show that homozygous Zeb1 ‐depletion in the germline results in a phenotype similar to the conventional Zeb1 knockout.